Biomechanics analysis for dominant leg during instep kicking - Mohd Firdaus, Mahamad Ali; Baba, Md. Deros; Ahmad Rasdan, Ismail (Penerbit Universiti Teknologi Malaysia, 2012)
This paper presents the 3D biomechanics analysis on a soccer player during performing instep kick. This study was conducted to investigate the significant correlation within variables, such as: approach angle, distance of supporting leg from the ball and ball internal pressure with respect to knee angular velocity of the ball on the kicking leg. Six subjects from different categories were selected to take part in this study. Subjects selected are using dominant right leg and free from any injury. Subjects were asked to perform one step instep kick according to the setting for the variables with different parameter. Data analysis was performed using 3 Dimensional "Qualisys Track Manager". Statistical analysis was conducted by using Microsoft Excel 2007 software. Taguchi statistical analysis method was used to determine the composition of L9 Orthogonal and larger noise to signal ratio (S/N). It was found the results of ANOVA analysis of P-values for all three parameters were lower than 0.05. It means that the approach angle, distance of supporting leg from the ball and the ball internal pressure have significant correlation with knee angular velocity.